2019
DOI: 10.1094/php-02-19-0014-br
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Quinone Outside Inhibitor Fungicides Conferred by the G143A Mutation in Cercospora sojina (Causal Agent of Frogeye Leaf Spot) Isolates from South Dakota Soybean Fields

Abstract: Resistance to quinone outside inhibitor (QoI) fungicides was detected in Cercospora sojina (causal agent of frogeye leaf spot) isolates collected from soybean (Glycine max) fields in four South Dakota counties during the 2018 growing season. A discriminatory dose assay was used to detect QoI-resistant isolates, and a follow-up polymerase chain reaction assay was used to determine the presence of the G143A mutation in QoI-resistant isolates. This is the first report of resistance to QoI fungicides in C. sojina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…For example, compared to the control, application of benomyl at different application timings based on growth stage did not significantly reduce frogeye leaf spot severity or associated grain yield loss on resistant soybean genotypes, although significant disease severity and yield loss reductions were observed with susceptible soybean genotypes [39]. Resistance within the targeted pathogen population to the active ingredient contained in the applied fungicide/s could also contribute to a positive relationship between fungicide use and yield losses [28, 29, 3133]. Furthermore, fungicides are applied with self-propelled, pull type, or aerial spray applicators in the U.S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, compared to the control, application of benomyl at different application timings based on growth stage did not significantly reduce frogeye leaf spot severity or associated grain yield loss on resistant soybean genotypes, although significant disease severity and yield loss reductions were observed with susceptible soybean genotypes [39]. Resistance within the targeted pathogen population to the active ingredient contained in the applied fungicide/s could also contribute to a positive relationship between fungicide use and yield losses [28, 29, 3133]. Furthermore, fungicides are applied with self-propelled, pull type, or aerial spray applicators in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…Fungicide resistance is an issue increasing in importance across soybean production areas in the U.S. as a result of automatic fungicide applications at specific growth stages, as well as fungicide applications with specific fungicide classes where the goal is a curative response [2831]. Currently, QoI fungicide resistance has been reported for several soybean pathogens in the U.S., including C. sojina , in Illinois, Tennessee [32], South Dakota [33], and Mississippi [29]. Zhang et al [31] recently reported QoI resistant C. sojina isolates from 14 states including Alabama, Arkansas, Delaware, Illinois, Indiana, Iowa, Kentucky, Louisiana, Mississippi, Missouri, North Carolina, Ohio, Tennessee, and Virginia.…”
Section: Introductionmentioning
confidence: 99%
“…Fungicide resistance is an issue increasing in importance across soybean production areas in the U.S. as a result of automatic fungicide applications at specific growth stages, as well as fungicide applications with specific fungicide classes where the goal is a curative response [28][29][30][31]. Currently, QoI fungicide resistance has been reported for several soybean pathogens in the U.S., including C. sojina, in Illinois, Tennessee [32], South Dakota [33], and Mississippi [29]. Zhang et al [31] recently reported QoI resistant C. sojina isolates from 14 states including Alabama, Arkansas, Delaware, Illinois, Indiana, Iowa, Kentucky, Louisiana, Mississippi, Missouri, North Carolina, Ohio, Tennessee, and Virginia.…”
Section: Plos Onementioning
confidence: 99%
“…For example, compared to the control, application of benomyl at different application timings based on growth stage did not significantly reduce frogeye leaf spot severity or associated grain yield loss on resistant soybean genotypes, although significant disease severity and yield loss reductions were observed with susceptible soybean genotypes [44]. Resistance within the targeted pathogen population to the active ingredient contained in the applied fungicide/s could also contribute to a positive relationship between fungicide use and yield losses [28,29,[31][32][33]. Furthermore, fungicides are applied with self-propelled, pull type, or aerial spray applicators in the U.S.…”
Section: Plos Onementioning
confidence: 99%
“…However, other mutations associated with resistance to QoI fungicides such as the F129L (change from phenylalanine to leucine at codon 129) and G137R (change from glycine to arginine at codon 137), have not been reported in C. sojina (Zeng et al, 2015). Since the first confirmation in 2010, QoI-resistant isolates have become widespread across more than 20 soybean-producing states in the U.S. (Harrelson et al, 2021;Mathew et al, 2019;Neves et al, 2020Neves et al, , 2021Neves et al, , 2022Standish et al, 2015;Zeng et al, 2015;Zhang et al, 2012aZhang et al, , 2012bZhang et al, , 2018Zhou & Mehl, 2020) (Figure 1.3).…”
Section: Fungicide Resistancementioning
confidence: 99%